Mistrial or Misdiagnosis: The Importance of Autopsy and Histopathological Examination in Cases of Sudden Infant Bronchiolitis-Related Death - Bertozzi, Giuseppe; Maglietta, Francesca; Baldari, Benedetta; Besi, Livia; Torsello, Alessandra; Di Gioia, Cira Rosaria Tiziana; Sessa, Francesco; Aromatario, Mariarosaria; Cipolloni, Luigi (Frontiers in Pediatrics, 2020)
Pediatrics, among all the branches of medicine, is a sector not particularly affected by a high number of claims. Nevertheless, the economic value of the compensation is significantly high, for example in cases of children who suffered multiple disabilities following perinatal lesions with a long-life expectancy. In Italy, the most of the claims for compensation concern surgical pathologies and infections. Among this latter, the dominant role is taken by respiratory tract infections. In this context, the purpose of this manuscript is to present a case series of infant deaths in different emergency-related facilities (ambulances, emergency rooms), denounced by relatives. Following these complaints, the autopsy was performed and subsequent histological examinations revealed the presence of typical and pathognomic histological findings of acute viral bronchiolitis, whose morphological appearance is poorly reported in the literature. The analysis of these cases made it possible to highlight the following conclusions: the main problems in diagnosing sudden death causes, especially in childhood, are the rapidity of death and the scarce correlation between the preexistent diseases and of the cause of death itself. For all these reasons, the autopsy, either clinical or medico-legal, is mandatory in cases of sudden unexpected infant death to manage claim requests, because only the histological examinations performed on samples collected during the autopsy can reveal the real cause of death.